2002
DOI: 10.1051/0004-6361:20011755
|View full text |Cite
|
Sign up to set email alerts
|

The Westerbork HI survey of spiral and irregular galaxies

Abstract: Abstract. Neutral hydrogen observations with the Westerbork Synthesis Radio Telescope are presented for a sample of 73 latetype dwarf galaxies. These observations are part of the WHISP project (Westerbork H  Survey of Spiral and Irregular Galaxies). Here we present H  maps, velocity fields, global profiles and radial surface density profiles of H , as well as H  masses, H  radii and line widths. For the late-type galaxies in our sample, we find that the ratio of H  extent to optical diameter, defined as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
391
4
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(421 citation statements)
references
References 30 publications
25
391
4
1
Order By: Relevance
“…The trend with M K is inverted; the most luminous galaxies contain the largest amount of gas, but the lowest relative gas content. Correlations with total luminosity, morphological type, and color are consistent with overall trends along the Hubble sequence and these trends are well known from previous studies (Roberts & Haynes 1994;Broeils & Rhee 1997;Verheijen & Sancisi 2001;Swaters et al 2002). The linear fits to the correlations are presented in the figure panels, as well as the Spearman rank-order coefficient (r s ) of the relations, calculated following Paper VIII.…”
Section: Hi Massessupporting
confidence: 86%
See 1 more Smart Citation
“…The trend with M K is inverted; the most luminous galaxies contain the largest amount of gas, but the lowest relative gas content. Correlations with total luminosity, morphological type, and color are consistent with overall trends along the Hubble sequence and these trends are well known from previous studies (Roberts & Haynes 1994;Broeils & Rhee 1997;Verheijen & Sancisi 2001;Swaters et al 2002). The linear fits to the correlations are presented in the figure panels, as well as the Spearman rank-order coefficient (r s ) of the relations, calculated following Paper VIII.…”
Section: Hi Massessupporting
confidence: 86%
“…Others point out the diversity in the radial behavior of Σ HI (R) in galaxies with a wide range of global properties (e.g., Verheijen & Sancisi 2001). Swaters et al (2002) found that the outer part of the Σ HI (R) profile in many late-type dwarf galaxies can be well fitted with an exponential decrease, and it can be argued that spiral galaxies in general should display a similar exponential profile at the outer radii. Here, we parameterize the typical radial behavior of Σ HI (R) and study its dependence on global photometric and kinematic properties of the galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…Note that f à also depends on the amount of metals present in dwarf galaxies, but the effects of metallicity will be smaller than the 2 orders-of-magnitude difference in f à . Figure 4 shows the distributions of exponential scale radii R d and central surface densities AE 0 for our model galaxies based on the standard model, compared with those for five BCDs by van Zee et al (1998) and a number of late-type dwarf galaxies by Swaters et al (2002). The scale radii and the surface densities of our model galaxies with M d ¼ 10 8 M and ¼ 0:035 and with M d ¼ 10 9 M and ¼ 0:05 at collapse redshift z ¼ 0 are consistent with the observed distributions.…”
Section: Modeling the Star Formation Ratementioning
confidence: 99%
“…5, but now with several observed distributions overlaid. The high column density regime is covered by the WHISP data (Swaters et al 2002;Noordermeer et al 2005) in H i emission; a Schechter function fit to this data by Zwaan et al (2005) is shown by the dashed line. The dash-dotted line shows H i emission data from the extended M 31 environment after combining data from a range of different telescopes (Braun & Thilker 2004).…”
Section: H I Distribution Functionmentioning
confidence: 99%